2008
DOI: 10.1111/j.1471-6712.2007.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting to being a father to an infant born prematurely: experiences from Swedish fathers

Abstract: The aim of this study was to describe the experiences of being a father to a prematurely born infant. Eight fathers of prematurely born children were interviewed using a narrative approach, and a thematic content analysis was used to analyse the interviews. The fathers described that the preterm birth gave them the chance to get to know their infant as they had to spend time at the intensive care unit. They also felt better educated by professionals who helped them take care of their infant. Their feelings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
132
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(154 citation statements)
references
References 29 publications
4
132
1
11
Order By: Relevance
“…Hammarstrand, Jönsson, and Hallström (2008), who evaluated a neonatal home care program, and Lindberg, Axelsson, and Ohrling (2008), describing fathers' adjustment to fatherhood, also found that coming home was associated with a sense of being a father. In the present study, the fathers felt that their child was healthy and they described this as having helped them to come to terms with the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Hammarstrand, Jönsson, and Hallström (2008), who evaluated a neonatal home care program, and Lindberg, Axelsson, and Ohrling (2008), describing fathers' adjustment to fatherhood, also found that coming home was associated with a sense of being a father. In the present study, the fathers felt that their child was healthy and they described this as having helped them to come to terms with the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be stated that fatherhood is a concept that has been changing drastically over the last few decades in the sense that fathers are getting closer to their children, interacting with them, and appearing interested and strongly active in their education (Camus & Frascarolo, 2003;Lindberg, Axelsson, & Öhrling, 2008). There are, in fact, several studies with results showing a more effective and affective paternal involvement (Fägerskiöld, 2006;Hossain, Roopnarine, Ismail, Hashmi, & Sombuling, 2007), showing that fathers desire to be present during the growth and development of their children.…”
mentioning
confidence: 99%
“…There are, in fact, several studies with results showing a more effective and affective paternal involvement (Fägerskiöld, 2006;Hossain, Roopnarine, Ismail, Hashmi, & Sombuling, 2007), showing that fathers desire to be present during the growth and development of their children. This change in the role of the father is multidimensional and encompasses several aspects, such as direct care provided to the child at any age (Camus & Frascarolo, 2003;Lamb, 1986;Lindberg et al, 2008;Simões, Leal, & Maroco, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Sweden 25 showed that encouragement of the father to spend more time in the treatment unit is a way to promote their familiarity with their preterm child and let them learn how to care for the baby. With the help of the care team, the fathers feel better prepared to be instructed by health professionals during hospitalization in the NICU and thus stronger and better equipped for the time of discharge.…”
mentioning
confidence: 99%